2021
DOI: 10.1098/rsob.210199
|View full text |Cite|
|
Sign up to set email alerts
|

Cell wall deficiency as an escape mechanism from phage infection

Abstract: The cell wall plays a central role in protecting bacteria from some environmental stresses, but not against all. In fact, in some cases, an elaborate cell envelope may even render the cell more vulnerable. For example, it contains molecules or complexes that bacteriophages recognize as the first step of host invasion, such as proteins and sugars, or cell appendages such as pili or flagella. In order to counteract phages, bacteria have evolved multiple escape mechanisms, such as restriction-modification, aborti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…3B and C ). This resembles our previously reported observations that described a phage-induced escape mechanism that allows the bacterial cell to shed its cell wall and thereby evade phage predation ( 12 , 19 ). By exposing these spherical cells to water, we observed that the majority of cells were lysed, which indicates that these are likely not spores but indeed cell wall-deficient cells as described in Ongenae et al ( 12 , 19 ) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…3B and C ). This resembles our previously reported observations that described a phage-induced escape mechanism that allows the bacterial cell to shed its cell wall and thereby evade phage predation ( 12 , 19 ). By exposing these spherical cells to water, we observed that the majority of cells were lysed, which indicates that these are likely not spores but indeed cell wall-deficient cells as described in Ongenae et al ( 12 , 19 ) (Fig.…”
Section: Resultssupporting
confidence: 90%
“…3B-C). This resembles our previously reported observations which described phage induced escape mechanism that allows the bacterial cell to shed its cell wall and thereby evade phage predation (13,19). By exposing these spherical cells to water, we observed that the majority of cells were lysed which indicates that these are likely not spores but indeed cell wall-deficient cells as described in Ongenae et al (13,19) (Fig.…”
Section: Bacteriophage Activity Can Be Detected For Other Organisms A...supporting
confidence: 90%
“…This may suggest that these diagnostic criteria and performance standards for antimicrobial susceptibility testing are not inclusive. For instance, cell wall deficiency has been recently proposed as an escape mechanism from phage infection 5 which has not been included in the latest versions of IDSA diagnostic criteria.…”
Section: Dear Editormentioning
confidence: 99%
“…In this state, the bacteria may be transiently protected against phages, because they lack the necessary entities that are required for phage binding and consequent infection. Since lack and/or deficiency of cell wall can be triggered by a range of antibiotic administration, phage escape is proposed as an undesirable repercussion 5 that can practically limit the use of phage therapy in special settings like hemodialysis units.…”
Section: Dear Editormentioning
confidence: 99%